2016
DOI: 10.1182/blood-2015-10-676700
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dual expression of MYC and BCL2 by immunohistochemistry on the risk of CNS relapse in DLBCL

Abstract: Key Points• Dual expression of MYC and BCL2 is associated with an increased risk of CNS relapse in DLBCL treated with R-CHOP.Dual expression of MYC and BCL2 by immunohistochemistry (IHC) is associated with poor outcome in diffuse large B-cell lymphoma (DLBCL). Dual translocation of MYC and BCL2, so-called "double-hit lymphoma," has been associated with a high risk of central nervous system (CNS) relapse; however, the impact of dual expression of MYC and BCL2 (dual expressers) on the risk of CNS relapse remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(126 citation statements)
references
References 35 publications
7
116
1
2
Order By: Relevance
“…Based on these results Fletcher and Kahl 2 recommended that patients with DLBCL and MYC rearrangements be considered at high risk of CNS relapse. In another recent study, Savage et al 29 reported that DLBCL patients and dual expression of MYC (≥40% positivity) and BCL2 (≥50% positivity) determined by immunohistochemistry, had higher risk of CNS relapse (2-year risk of 9.7% vs. 2.2%, P=0.001). This study also showed increased risk for those patients with activated B-cell or non-germinal center B-cell origin, but significance was not retained in the multivariate analysis.…”
Section: Guidelines For Diagnosis Prevention and Management Of Centrmentioning
confidence: 99%
“…Based on these results Fletcher and Kahl 2 recommended that patients with DLBCL and MYC rearrangements be considered at high risk of CNS relapse. In another recent study, Savage et al 29 reported that DLBCL patients and dual expression of MYC (≥40% positivity) and BCL2 (≥50% positivity) determined by immunohistochemistry, had higher risk of CNS relapse (2-year risk of 9.7% vs. 2.2%, P=0.001). This study also showed increased risk for those patients with activated B-cell or non-germinal center B-cell origin, but significance was not retained in the multivariate analysis.…”
Section: Guidelines For Diagnosis Prevention and Management Of Centrmentioning
confidence: 99%
“…15 In an analysis from the British Columbia database, ;10% of patients with double-expressor lymphoma (including a subset with double-hit lymphoma) subsequently relapsed in the CNS. 33 For these reasons, unlike the situation with routine DLBCL, I recommend baseline lumbar puncture and CSF sampling in most patients with double-hit lymphoma. Exceptions include patients who present with early-stage disease, where CSF involvement is much less common, or frail elderly patients, where treatment with curative intent is contraindicated.…”
Section: How Do I Evaluate Patients With Double-hit Lymphoma?mentioning
confidence: 99%
“…In addition, these patients frequently present with a central nervous system relapse, which is always associated with poor outcome. 10 There is typically a clonal evolution among lymphoma cells, with some heterogeneity of genes involved in lymphoma growth that might explain the chemorefractoriness and difficulties of salvage. 11 Furthermore, it has also been shown that DLBCL pathogenesis is strongly related to epigenetic perturbations and that high epigenomic heterogeneity correlated with a higher relapse rate and poor outcome.…”
Section: Patients With Early Relapsementioning
confidence: 99%